Investigation of discriminate and indiscriminate use of doxycycline in broiler: an indoor research on antibiotic doxycycline residue study in edible poultry tissue - Ali, Md Rostom; Sikder, Md Mahmudul Hasan; Islam, Md Shakil; Islam, Md Shafiqul (Asian Journal of Medical and Biological Research, 2020)
Abuse of antibiotics is more common in developing countries including Bangladesh. The aim of this study was to detect doxycycline residue after discriminate and indiscriminate administration in broiler poultry. Eighteen broiler chicks, DOC (Cobb-500) was collected & reared up to 31 days. On day 16, they were randomly divided into 3 groups, namely group–A (Control group), group-B (Discriminate group) and group-C (Indiscriminate group). Each group contains 6 birds. The discriminate and indiscriminate groups were treated with antibiotic, doxycycline. In group-B withdrawal period was followed by treatment for 7 days. On the other hand, withdrawal period was not maintained in group-C, i.e. the antibiotic treatment was continued until the day of sacrifice. TLC analysis revealed that intensity of doxycycline in discriminate antibiotic group for liver, kidney, thigh muscle and breast muscle samples were found 63.33%, 65.33%, 22.67% and 26.00% respectively. And in indiscriminate antibiotic group intensity of doxycycline for liver, kidney, spleen, thigh muscle and breast muscle samples were found 50.67%, 50.33%, 39.50% and 48.17% respectively. All the samples of control group were found 0% intensity. The different among intensity were statistically significant. Overall, the present study documented the widespread abuse of doxycycline and failure to implement the recommended withdrawal period will undeniably leads to deposition of residues in broiler tissues. Asian J. Med. Biol. Res. March 2020, 6(1): 1-7